Ewolucja zmian przepisów prawnych o odpadach niebezpiecznych oraz ich związek z pożarami składowisk i miejsc magazynowania odpadów - Kierzkowska, Joanna (Studia Prawnoustrojowe, 2019)
The research is devoted to showing the evolution of changes in legal regulations on hazardous waste and their connection to fires in storage and disposal sites in Poland. The first part examines the evolution of EU regulations on the codes of hazardous waste properties. The second research area, on the other hand, is associated with fires on landfills taking into account the hazardous waste context and shows the latest amended regulations to prevent their occurrence.